The Effectiveness of Zikir Therapy in Reducing Anxiety in Stage 2 Colon Cancer Patients Before Undergoing Chemotherapy - Marselina, Seli; Purbasari, Dwiyanti (INDOGENIUS, 2025)
Background & Objective: Anxiety is an emotional response that often arises in cancer patients before undergoing chemotherapy. High levels of anxiety can have a negative impact on the physiological and psychological condition of patients. Zikir therapy is one non-pharmacological intervention that can be used to help reduce anxiety through a spiritual approach. This study aims to determine the effectiveness of zikir therapy in reducing anxiety in colon cancer patients before undergoing chemotherapy in the HOT (Hematology Oncology Treatment) Room at RSD Gunung Jati Hospital in Cirebon City. Method: This study employed a qualitative approach with a case study design involving three patients experiencing anxiety prior to chemotherapy. Data were collected through interviews, observations, and assessments of vital signs before and after zikir therapy was administered. Result: The study results showed that after receiving zikir therapy, there was a reduction in anxiety symptoms and signs in all three patients, both subjectively and objectively. Patients felt calmer, blood pressure and heart rate decreased, and no longer appeared restless or pale. Conclusion: It can be concluded that zikir therapy is effective as a nursing intervention in reducing anxiety in colon cancer patients before undergoing chemotherapy.